2023
DOI: 10.1002/acn3.51859
|View full text |Cite
|
Sign up to set email alerts
|

Association between brain health outcomes and metabolic risk factors in persons with diabetes

Evan L. Reynolds,
Kristen Votruba,
Clifford R. Jack
et al.

Abstract: We performed a cross‐sectional study to determine associations between cognition and MRI‐derived brain outcomes, with obesity, diabetes duration, and metabolic risk factors in 51 Pima American Indians with longstanding type 2 diabetes (T2d) (mean [SD] age: 48.4 [11.3] years, T2d duration: 20.1 [9.1] years). Participants had similar cognition (NIH Toolbox Cognition Battery composite: 45.3 [9.8], p = 0.64, n = 51) compared to normative data. T2d duration, but not other metabolic risk factors, associated with dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The main goal of each reviewed study was to assess the regional effects of T2D, whether in the presence or absence of other conditions, on cerebral cortical thickness as measured on T1-weighted MRI. Some studies dug deeper by, for example, evaluating the association between cognitive function and brain morphology in T2D patients, including the effect of various confounders such as age, years of education, and disease duration (Peng et al, 2014 ; Reynolds et al, 2023 ); investigating the relationship between fasting and non-fasting physiology with gray matter and white matter volume (Markus et al, 2017 ; Honea et al, 2022 ); measuring the association between neuropsychological deficits with structural and functional brain alternations (Garcia-Casares et al, 2014 ; Zhang et al, 2022 , 2023 ); or comparing the effect of metabolic and vascular factors on cortical and subcortical gray matter structural alterations (Korf et al, 2006 ; Brundel et al, 2010 ; Tchistiakova et al, 2014 ; Bernardes et al, 2018 ; Cui et al, 2023 ; Moreno et al, 2023 ; Reynolds et al, 2023 ). Other studies compared the impact of T2D on brain morphology not only against controls, but also prediabetes (Jing et al, 2023 ; Monereo-Sánchez et al, 2023 ), major depression (Ajilore et al, 2010 ) or mild cognitive impairment and Alzheimer's disease (Moran et al, 2019 ; Palix et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of each reviewed study was to assess the regional effects of T2D, whether in the presence or absence of other conditions, on cerebral cortical thickness as measured on T1-weighted MRI. Some studies dug deeper by, for example, evaluating the association between cognitive function and brain morphology in T2D patients, including the effect of various confounders such as age, years of education, and disease duration (Peng et al, 2014 ; Reynolds et al, 2023 ); investigating the relationship between fasting and non-fasting physiology with gray matter and white matter volume (Markus et al, 2017 ; Honea et al, 2022 ); measuring the association between neuropsychological deficits with structural and functional brain alternations (Garcia-Casares et al, 2014 ; Zhang et al, 2022 , 2023 ); or comparing the effect of metabolic and vascular factors on cortical and subcortical gray matter structural alterations (Korf et al, 2006 ; Brundel et al, 2010 ; Tchistiakova et al, 2014 ; Bernardes et al, 2018 ; Cui et al, 2023 ; Moreno et al, 2023 ; Reynolds et al, 2023 ). Other studies compared the impact of T2D on brain morphology not only against controls, but also prediabetes (Jing et al, 2023 ; Monereo-Sánchez et al, 2023 ), major depression (Ajilore et al, 2010 ) or mild cognitive impairment and Alzheimer's disease (Moran et al, 2019 ; Palix et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Disease duration in T2D patients was statistically shown to be a factor related to cortical/sub-cortical decline in almost all studies. Specifically, Reynolds et al ( 2023 ), found that longer duration of T2D is associated with reduced cortical thickness, gray matter volume, subcortical gray matter volume, and increased white matter hyperintensity volume. Only one discordant report concluded that T2D duration was not correlated with hippocampal volume (Li M. et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%